Development, Education and Socialization of the Personality of the Child - Makhanbetovna, Sarsenbayeva Raikhon (European Journal of Life Safety and Stability (2660-9630), 2023)
This article contains information about the development, upbringing and socialization of the child's personality. In particular, information about personality, the concept of personality, personality development, and personality socialization, general mechanisms of socialization, axiological approach and factors influencing the formation of a child's personality are covered: heredity, environment and upbringing.